FORMULASI KRIMINALISASI ILLICIT ENRICHMENT DALAM TINDAK PIDANA KORUPSI SEBAGAI UPAYA MENYELAMATKAN ASET NEGARA - Alya Syarifa Tsany (2022)
Corruption case get increased in Indonesia caused by the eradication of corruption is not optimal. Indonesia has ratifying the United Nation Convention Against Corruption (UNCAC) through Law Number 7 of 2006. One of the acts of corruption regulated in UNCAC is Illicit Enrichment, which is a criminal act of self enrichment committed by state officials. The problem in this study is how to formulate illicit enrichment criminalization through non-conviction based asset forfeiture actions as an effort to save state assets. Based on the type, this research is a normative legal research that uses secondary and tertiary data sources. Data analysis using statute approach and conceptual approach. The results of this study indicate that the concept of criminalization of Illicit Enrichment must be applied in positive law and combined through a system of proof against the confiscation of assets without punishment or non-conviction based asset forfeiture, of course by still paying attention to human rights. This solution is also expected to be able to increase the return of state assets from the Illicit Enrichment. Keyword: Corruption, Illicit Enrichment, Shifting Burden of Proof, Non-Conviction Based Asset Forfeiture.